Investigation into the long-term effects of static and PNF stretching exercises on range of motion and jump performance - (:unkn) unknown (My University, 2009)
The purpose of the present study was to investigate the long-term effects of two different stretching techniques on the range of motion (ROM) and on drop jump (DJ). DJ scores were assessed by means of a contact mat connected to a digital timer. ROM was measured by use of a goniometer. The training was carried out four times a week for 6 weeks on 10 subjects as passive static stretching (SS), and on 9 subjects as contract-relax PNF (CRPNF) stretching. The remaining nine subjects did not perform any exercises (control group). One-way Analysis of Variance (ANOVA) results indicated that the differences among groups on DJ were not statistically different (F(2,27)=.41, p>.05). ROM values were significantly higher for both stretching groups, while no change was observed for the control group. In conclusion, static and proprioceptive neuromuscular facilitation (PNF) stretching techniques improved the ROM, but neither of the stretching exercises had any statistically significant effect on the DJ scores. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Drop jump; PNF; Range of motion; Static stretching